2014
DOI: 10.1128/mcb.00324-14
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor/MAZ-Dependent Induction of Caveolin-1 Regulates Colon Permeability through Suppression of Occludin, Leading to Hypoxia-Induced Inflammation

Abstract: c Caveolae are specialized microdomains on membranes that are critical for signal transduction, cholesterol transport, and endocytosis. Caveolin-1 (CAV1) is a multifunctional protein and a major component of caveolae. Cav1 is directly activated by hypoxia-inducible factor (HIF). HIFs are heterodimers of an oxygen-sensitive ␣ subunit, HIF1␣ or HIF2␣, and a constitutively expressed ␤ subunit, aryl hydrocarbon receptor nuclear translocator (ARNT). Whole-genome expression analysis demonstrated that Cav1 is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 55 publications
3
62
0
Order By: Relevance
“…Indeed, IR increased ROS in the intestine followed by the direct recruitment of HIF-1α to the Wnt2b promoter and subsequent Wnt2b transactivation (see Figures 4J, 4P). Furthermore, given the inhibitory effects of Chet on both HIF-1α and HIF-2α and the protective role of HIF-2α in the intestine (Taniguchi, et al, 2014; Xie, et al, 2014), HIF-2α might also be involved in ROS-mediated Wnt2b transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IR increased ROS in the intestine followed by the direct recruitment of HIF-1α to the Wnt2b promoter and subsequent Wnt2b transactivation (see Figures 4J, 4P). Furthermore, given the inhibitory effects of Chet on both HIF-1α and HIF-2α and the protective role of HIF-2α in the intestine (Taniguchi, et al, 2014; Xie, et al, 2014), HIF-2α might also be involved in ROS-mediated Wnt2b transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial roles are likely mediated through inhibiting SOCE and the expression of SOCCs channel protein TRPCs, which then lead to suppressed proliferation and migration of PASMCs (11,13). Previous studies have reported that, in cancer cell lines, caveolin-1 acts as a direct transcription target of the main hypoxic regulator, hypoxia-inducible factors 1 and 2, and facilitates the proproliferative consequences during the process of tumorigenesis (47,48). Interestingly, the effects of PPARg on caveolin-1 vary considerably in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Colon permeability was assessed with FITC-labeled dextran (FD4; Sigma-Aldrich) as previously described (41). Quantitative Real-Time RT-PCR.…”
Section: Methodsmentioning
confidence: 99%